2019
DOI: 10.1039/c9ra03814k
|View full text |Cite
|
Sign up to set email alerts
|

A study on the local corrosion behavior and mechanism of electroless Ni–P coatings under flow by using a wire beam electrode

Abstract: The local corrosion behavior and mechanism of Ni–P coatings in an NaCl solution with different flow speeds were investigated through a wire beam electrode with morphological, elemental and electrochemical analyses as well as numerical simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Later it was used to quantify the electrochemical inhomogeneity on oil-painted metal and the protective ability of rustproofing oil coating [5,15,104–113]. Electrode arrays of various designs were also used in various experiments, often together with electrochemical impedance measurements, for assessing the anti-corrosion performance of protective polymer coatings such as epoxy coatings [114116], waterborne coatings [117,118], Ni-P coatings [119], enamel coatings [120] and anti-corrosion oil films [121].…”
Section: Electrode Array Probes Designed For Various Applicationsmentioning
confidence: 99%
“…Later it was used to quantify the electrochemical inhomogeneity on oil-painted metal and the protective ability of rustproofing oil coating [5,15,104–113]. Electrode arrays of various designs were also used in various experiments, often together with electrochemical impedance measurements, for assessing the anti-corrosion performance of protective polymer coatings such as epoxy coatings [114116], waterborne coatings [117,118], Ni-P coatings [119], enamel coatings [120] and anti-corrosion oil films [121].…”
Section: Electrode Array Probes Designed For Various Applicationsmentioning
confidence: 99%
“…The way for processing substrate can be found in the published literature. 20) Third, the achieved NiP coating was placed in a furnace, the rate of temperature increased in the furnace was 10°C/min. The coating was kept the temperature at 400°C for 1 hour and cooled in the furnace for 20 minutes, then taken it out, the NiP coating (NiP) and the heat-treated NiP coating (h-NiP) as a comparison.…”
Section: Electroless Nip Coatingmentioning
confidence: 99%
“…Wire beam electrode (WBE) is an electrochemical testing technology from the 1990s [14]. Different from the traditional monolithic electrode, WBE is a multi-electrode, which helps get the electrochemical information of the local area on the surface of the working electrode, and is used to study the mechanism of crevice corrosion [15,16]. Wang et al [17] found that LAM Hastelloy C22 was more resistant to corrosion in oxidising acid because a dense oxide film formed, while it showed obvious local corrosion in hydrochloric acid.…”
Section: Introductionmentioning
confidence: 99%